2022
DOI: 10.3390/biology11060808
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Biologic Therapy and the Importance of Multidisciplinary Approach for an Accurate Management of Patients with Moderate-Severe Psoriasis and Concomitant Diseases

Abstract: Psoriasis is a chronic multisystem inflammatory disease associated with a plethora of comorbidities including metabolic syndrome, cardiovascular disease, hypertension, diabetes, hyperlipidemia, obesity, anxiety, depression, chronic kidney disease, and malignancy. Advancement in unveiling new key elements in the pathophysiology of psoriasis led to significant progress in the development of biologic agents which target different signaling pathways and cytokines involved in the inflammatory cascade responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…An in-depth understanding of the pathophysiology of psoriasis led to significant advances in the development of safe and efficient novel therapeutic options, with four classes of biologic therapy being approved for the management of moderate to severe psoriasis: TNF-α inhibitors, anti-IL-23 agents, anti-IL-12/23 agents, IL-17 inhibitors, as well as small-molecule inhibitors, such as apremilast, as presented in Table 1 [26]. Nevertheless, in many instances, the concomitant diseases associated with psoriasis greatly impact the clinical decision of selecting one therapeutic class over another [26,27]. Therefore, when planning an individualized therapeutic approach, it is recommended to carefully take into consideration which biologic agent improves or exacerbates a certain comorbidity for each patient, as presented in Table 2 [26].…”
Section: Cells T Helpermentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth understanding of the pathophysiology of psoriasis led to significant advances in the development of safe and efficient novel therapeutic options, with four classes of biologic therapy being approved for the management of moderate to severe psoriasis: TNF-α inhibitors, anti-IL-23 agents, anti-IL-12/23 agents, IL-17 inhibitors, as well as small-molecule inhibitors, such as apremilast, as presented in Table 1 [26]. Nevertheless, in many instances, the concomitant diseases associated with psoriasis greatly impact the clinical decision of selecting one therapeutic class over another [26,27]. Therefore, when planning an individualized therapeutic approach, it is recommended to carefully take into consideration which biologic agent improves or exacerbates a certain comorbidity for each patient, as presented in Table 2 [26].…”
Section: Cells T Helpermentioning
confidence: 99%
“…Nevertheless, in many instances, the concomitant diseases associated with psoriasis greatly impact the clinical decision of selecting one therapeutic class over another [ 26 , 27 ]. Therefore, when planning an individualized therapeutic approach, it is recommended to carefully take into consideration which biologic agent improves or exacerbates a certain comorbidity for each patient, as presented in Table 2 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies developed on psoriatic patients have shown that therapies addressing signaling pathways and cytokines can affect also the concurrent diseases of the patient [4]. The gutskin axis functions both ways, as the imbalanced gut microbiome can modulate the clinical outcome of PSO.…”
Section: Introductionmentioning
confidence: 99%